1952
DOI: 10.1039/tf9524800812
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive tracer studies of free radical mechanisms. Part 1.—The photolysis of acetone + iodine mixtures

Abstract: The photolysis of acetone has been investigated in the presence of the vapour of iodine labelled with radioactive 1311, using the output of a high-pressure mercury arc filtered so as to give only radiation in the neighbourhood of 3 130 A. The iodine quenches almost completely the secondary reactions of the radicals produced in the photolysis, but appears also to have a specific deactivating effect on one of the activated molecules involved in the photolysis, with the result that the quantum yield of methyl iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1952
1952
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The literature on the photochemistry of acetone is extensive and thorough and has been previously reviewed. ki (7) There are however several points of disagreement in the literature concerning this mechanism. Thus Noyes and Dorfman6 found values of a (~k\/(k\ + k2)) of 0.07 and 0.22 at 313 and 254 nm, while Martin and Sutton7 found a = 0 at 313 nm and concluded it likely that a = 0 at 254 nm.…”
mentioning
confidence: 99%
“…The literature on the photochemistry of acetone is extensive and thorough and has been previously reviewed. ki (7) There are however several points of disagreement in the literature concerning this mechanism. Thus Noyes and Dorfman6 found values of a (~k\/(k\ + k2)) of 0.07 and 0.22 at 313 and 254 nm, while Martin and Sutton7 found a = 0 at 313 nm and concluded it likely that a = 0 at 254 nm.…”
mentioning
confidence: 99%
“…Remaining for discussion are the results of experiments performed at 50" and 100" C. Other reactions generally considered to take place in photolysis below 100" C are 2CH3CO -+ (CH3CO)z (6) (7) CH3 + CH3CO -+ CH3COCH3. 11). Using the values given above one can calculate that deactivation is unlikely in the presence of 10 mm of acetone at 100" C. Indeed the quantum yield is near unity.…”
Section: Second-order Decomposition Of Acetyl Radicalsmentioning
confidence: 96%
“…In the photolysis of acetone an iodine pressure of a few millimeters is sufficient to reduce the quantum yields of ethane, methane, and carbon monoxide by more than a factor of 100. The products of the reaction of the methyl and acetyl radicals with iodine are methyl iodide and probably acetyl iodide (10,36,37,66,90). Unfortunately, most investigators have found that acetyl iodide is particularly difficult to determine.…”
Section: B Photolysis In the Presence O F Iodinementioning
confidence: 97%
“…It may undergo further reaction, but it evidently does not decompose to give carbon monoxide in appreciable quantities. In experiments done with radioactive iodine during which separation was made by carrier gas, the acetyl iodide vaned from 3 to 120 per cent of the methyl iodide under otherwise identical conditions (66).…”
Section: B Photolysis In the Presence O F Iodinementioning
confidence: 99%